Analisis Pengaruh Pertumbuhan Ekonomi, Pendidikan, dan Pengangguran terhadap Kemiskinan Di Kota Malang - Meylana Widya Mindayanti; Wiwin Priana Primandhana; Mohammad Wahed (Syntax Idea, 2021)
This study was conducted to find out the influence between the economic growth, education, unemployment, and poverty in Malang City from 2005 to 2019. Secondary data of the study was obtained through the Central Bureau of Statistics website in East Java and Malang City. The method used was quantitative research using Multiple Linear Regression Analysis with Ordinary Least Square (OLS) model. From the results of the study can be concluded that economic growth has a positive and significant impact on poverty in Malang City. This is known according to t count more than t table (2.668 ≥ 2.201) and the significance level of 0.022. On the other hand, education cannot significantly influence the poverty in Malang City with the t count less than t table (1.309 ≤ 2.201) and seen from the significance level of 0.217. Meanwhile, unemployment has a positive and significant impact on the poverty in Malang City seen from the t count more than t table (6.052 ≥ 2.201) and from the significance level of 0.000.